Frictional behaviour of AA7050/7.5B4Cp/Gr hybrid composites fabricated through stir casting. Issue 1 (February 2021) - Ranjith, R; Venkatesan, S; Sivakumar, N S; Naresh Kumar, P
Abstract: In this research, AA7050 aluminium alloy strengthened with Boron carbide (B4 Cp ) and Graphite (Gr) was manufactured by stir casting. The impact of the reinforcing particles on various process parameters on the friction coefficient were thoroughly examined utilizing pin-on-disc apparatus with experiments centred on design of experiments. The outcomes exposed that the coefficient of friction decreases with upsurge in percentage reinforcement and increases with applied load, and sliding distance. With respect to the sliding velocity it decreases until a saddle point, there after it starts to increase. Utilising the response surface methodology, a mathematical model for the friction coefficient was established.